Aristo of Ceos : Text, Translation, and Discussion - Fortenbaugh, William (Rutgers University Studies in Classical Humanities, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Contributors -- 1. Aristo of Ceos: The Sources, Text and Translation -- 2. In Search of Aristo of Ceos -- 3. I frammenti papiracei di Aristone di Ceo -- 4. L'Autore del Περì τoυ̑ κoυϕíζειν ὑπερηϕανíας: Un problema riaperto -- 5. Characters in Aristo -- 6. Aristo on Blends of Arrogance -- 7. Aristo of Ceos in the Greek Gnomologies -- 8. Natural Philosophy in the Peripatos after Strato -- 9. Peripatetic Biology and the Epitome of Aristophanes of Byzantium -- Index of Ancient Sources for Chapters 2-9.